MODEL PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN PAI DI SMPN 2 PAMEKASAN - Arif, Saiful (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2016)
This result of research articleÂ  is describing about instructional contextual models on the subject Islamic education in SMPN 2 Pamekasan. There are three focus of it: the first, how is the perception of teacher of Islamic education on instructional contextual models in the SMPN 2 Pamekasan? Second, how is the activities instructional contextual models in on Islamic education the SMPN 2 Pamekasan? Third how is the respons of students on the instructional contextual models in on Islamic educationÂ  in the SMPN 2 Pamekasan?. ByÂ  this research has got information about: 1) Perceptionâs of Islamic education teacher about instructional contextual models in theÂ  SMPN 2 Pamekasan. 2) the activities of instructional contextual models on Islamic education in the SMPN 2 Pamekasan, and 3) the respons students on theÂ  instructional contextual models in on Islamic educationÂ  in the SMPN 2 Pamekasan